The Role of Radiation Therapy in Targeted Cancer Treatment: Innovations and Challenges - Kazem, Khudair Abis; Kazem Abd, Muhammad Fadel; Kazim, Ibrahim Jassim; Asaad Hassan Karam Jaber; Hajhuj, Hadeel Ahmed (American Journal of Botany and Bioengineering, 2024)
Radiation therapy plays a significant role in targeted cancer treatment. It has been known for more than a hundred years. Radiation oncology combines advances in cancer biology, accelerating radiation machines, new imaging technologies for cancer visualization, and refinements in defining tumor contours with advances in computer technologies, leading to the development of practice-changing targeted cancer treatment. New strategies for targeted radiation are under investigation, such as dose escalation using improved imaging methods for tumor definition and dose reduction for normal tissues using increased precision of radiation delivery, leading to new treatment approaches of dose painting, tumor sub-volume therapy, and site-specific intensity-modulated radiation therapy. Recent advances in radiologic imaging methods and computer technologies have the potential to change radiation oncology significantly by allowing assessment of tumor function, quantification or biological targeting of tumor markers, real-time tumor positioning, adaptation, and treatment delivery. These advanced techniques make radiotherapy more effective in destroying tumor cells and less harmful to healthy tissues. Targeted radiation treatment is increasingly available at academic medical centers worldwide. Recent innovations in diagnostic imaging, chemotherapy drugs, and surgery have raised the bar for the role of radiation therapy in modern multimodal cancer care. The advanced targeted radiation techniques are underutilized and still face many challenges in taking these advancements from research to real-world applications for cancer patients. This essay explores various innovative radiation technical advancements and discusses the challenges to improving clinical outcomes using these advanced techniques as part of multimodal cancer care.